PENGGUNAAN INSTAGRAM SEBAGAI TREND MEDIA DAKWAH MASA KINI STUDI AKUN INSTAGRAM PONDOK PESANTREN NURUL JADID - zakiyah romadlany (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2019)
Abstract: This article explains about the use of Instagram as a contemporary media propaganda trend. The rise of social media made the preachers intrigued to channel their da'wah using Internet networks. Media is a tool for channeling communication to other people. While da'wah is inviting others to goodness. If it is concluded, the da'wah media is a tool to invite others to a better way. Media Instagram is a very interesting media to be used as a media for propaganda. Remembering da'wah can use images and audio visuals. This research is a case study of the mahasantri response to da'wah messages contained in the Instagram account of Pondok Pesantren Nurul Jadid (PPNJ). Qualitative descriptive method becomes a method to help researchers analyze the collected data. Based on collected data. Showing good response and the message posted is used as a reference or motivation to be better. Keywords: instagram, da'wah media, da'wah message, response.